A case of an anaplastic meningioma metastasizing to the mediastinal lymph nodes. (3rd July 2016) - Nishida, Norihiro; Kanchiku, Tsukasa; Imajo, Yasuaki; Suzuki, Hidenori; Yoshida, Yuichiro; Kato, Yoshihiko; Hoshii, Yoshinobu; Taguchi, Toshihiko
Abstract : Context : Grade II and III (World Health Organization classification) meningiomas rarely develop in the spinal cord. However, we experienced a case with an anaplastic meningioma that developed in the spinal cord at the cervicothoracic junction and metastasized to the mediastinal lymph nodes. No such cases have previously been reported. Findings : The patient was a 68-year-old man who developed back pain that did not affect his daily living. He developed left lower limb paralysis, and was admitted after magnetic resonance imaging (MRI) revealed an intramedullary tumor at the level of cervical vertebra 7 and thoracic vertebra 1. Positron emission tomography revealed tracer uptake in the intramedullary tumor and the mediastinal lymph nodes, suggesting a metastatic spinal cord tumor or malignant lymphoma. A lymph node biopsy was then performed. Although the tumor was highly malignant, its primary site was not identified. Detailed examinations by several other departments revealed no abnormalities. On hospital day 30, his left lower limb paralysis deteriorated, and MRI revealed that the tumor had grown. Thus, laminaplasty, laminectomy, and tumor resection were performed. The tumor was an anaplastic meningioma that resembled mediastinal lymph node tissue, and other tumor lesions were not found. These findings suggested that an anaplastic meningioma had metastasized to the mediastinal lymph nodes. The patient did not respond to radiotherapy, and he was transferred to another hospital. Conclusion : In cases of intramedullary spinal tumors with metastasis without other potential primary tumor lesions, early diagnosis and treatment should be performed while considering anaplastic meningioma.